Back to Buchanan? Explorations of welfare and subjectivism in behavioral economics - Malte Dold (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2017)
In light of behavioral findings regarding inconsistent individual decision-making, economists have begun to re-conceptualize the notion of welfare. One prominent account is the preference purification approach (PP), which attempts to reconstruct preferences from revealed choices based on a normative understanding of neoclassical rationality. Using Buchanan's notion of creative choice, this paper criticizes PP's epistemic, ontological, and psychological assumptions. It identifies PP as a static position that assumes the satisfaction of given 'true preferences' as the normative standard for welfare. However, following Buchanan, choice should be understood dynamically as a process whereby preferences constantly regenerate. Accordingly, the meaning of welfare emerges from an ongoing quest for individual self-constitution. If this holds true, then rationality axioms cannot serve as a priori normative standards. Instead, creative imagination and learning processes must re-main central to any understanding of welfare in economics.
Keywords: B41; D03; P46; 330; Behavioral Welfare Economics; Creative Choice; James M. Buchanan; Rationality; Methodology; Subjectivism